2018
DOI: 10.1287/msom.2018.0706
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Special Issue on Research at the Interface of Finance, Operations, and Risk Management (iFORM): Recent Contributions and Future Directions

Abstract: Abstract. Interface of finance, operations, and risk management (iFORM) is a relatively new research area dealing with timely, complex, and boundary-spanning issues in a variety of settings from start-ups to global enterprises. iFORM research addresses ways to better integrate physical, financial, and informational flows by combining the operational choices of the firm with its financial decisions, and merging information flows between the firm and its customers and suppliers with informational flows between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 79 publications
(91 reference statements)
0
70
0
Order By: Relevance
“…The present study also belongs to the nascent literature on the operations–finance interface, including joint operational and financial risk management of firms, supply chain finance, and contracts between the firm and its financiers/investors (Zhao and Huchzermeier, 2015; Babich and Kouvelis, 2018; Ivanov, 2018). Some investigators have studied capital‐constrained firms’ purchasing decisions together with financial considerations such as discounting or factoring (Choi, 2016; Li and Gu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present study also belongs to the nascent literature on the operations–finance interface, including joint operational and financial risk management of firms, supply chain finance, and contracts between the firm and its financiers/investors (Zhao and Huchzermeier, 2015; Babich and Kouvelis, 2018; Ivanov, 2018). Some investigators have studied capital‐constrained firms’ purchasing decisions together with financial considerations such as discounting or factoring (Choi, 2016; Li and Gu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Babich and Kouvelis () conduct a compressive literature review on the interface of finance, operations, and risk management, and summarize that current research in this domain includes SCF (trade credit and buyer‐intermediated finance and their effects on supply chain performance), agency problems (risk shifting and managerial short‐termism and their influence on operational decisions), contracting between the firm and its investors and how it alters contracting with supply chain partners, and supply risk management with commodity price fluctuations. Within the literature related to SCF, several clusters are focused on operational decisions, trade credit, and contract coordination in SCF.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the benefits of SCF that the literature has widely highlighted is the reduction of cost of financing (Van der Vliet et al 2015;Iacono et al 2015;Gelsomino et al 2016b;Zheng and Zhang 2017;Ding et al 2017;Babich and Kouvelis 2018;Yu and Zhu 2018;Yang et al 2018). It helps to facilitate offering finance at a lower cost to the SC partners, who generally are not privileged to receive capital at lower cost.…”
Section: The Outcome Of Supply Chain Financingmentioning
confidence: 99%
“…It leads to financial service providers extending finance at lower interest rates. Supply chain finance not only facilitates a lower cost of financing, it also helps reduce the overall cost in the supply chain, e.g., cost of producing and delivering goods/services (Blackman and Holland 2006;Iacono et al 2015;Gelsomino et al 2016b;Jiang et al 2016;Liu and Wen 2017;Babich and Kouvelis 2018). SCF has been widely touted to offer solutions to the problems faced by SMEs in availing finance; the literature on SCF revealed that SCF improves the accessibility to funds, particularly for smaller SC partners (Suayb Gundogdu 2010; Wang et al 2012;Yan and Sun 2015;Hofmann and Zumsteg 2015;Liu and Wen 2017;Ding et al 2017;Chen and Wen 2017;Zheng and Zhang 2017;Li et al 2011).…”
Section: The Outcome Of Supply Chain Financingmentioning
confidence: 99%
See 1 more Smart Citation